2021
DOI: 10.1002/adhm.202100412
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradable Copper‐Based Nanoparticles Augmented Chemodynamic Therapy through Deep Penetration and Suppressing Antioxidant Activity in Tumors

Abstract: Chemodynamic therapy (CDT) efficacy has been limited by the poor penetration ability of large nanoparticles (NPs) and the antioxidant activity of tumors, especially high heme oxygenase (HO-1) and glutathione (GSH) levels. Herein, PEGylated CuMoO x -coated and zinc protoporphyrin IX (ZP)-loaded Cu (CCMZ) NPs are designed to afford rapid degradation ability and augmented CDT efficacy through inhibiting HO-1 activity and depleting GSH. The deep penetration of tumor can be achieved under the high levels of GSH, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(26 citation statements)
references
References 44 publications
0
26
0
Order By: Relevance
“… 146 , 147 Secondly, regulating the TME to enhance CDT performance, such as increasing H 2 O 2 concentration in tumor, 148 , 149 and reducing the excessive intracellular antioxidant GSH, 150 can improve efficiency of CDT. 151 In addition, CDT-based combination therapy can be developed, such as CDT-PDT, 152 CDT-PTT, 153 , 154 CDT-chemotherapy, 155 CDT-immunotherapy, 156 CDT-RT, 157 CDT-SDT, 158 CDT-starvation therapy, 159 which can produce significant synergistic effects and reduce the side effects of CDT agents. However, in order to address the current barriers of CDT for clinical applications, we should try to avoid large doses, complex synthesis processes and cumbersome auxiliary devices when designing nanoplatforms.…”
Section: Discussionmentioning
confidence: 99%
“… 146 , 147 Secondly, regulating the TME to enhance CDT performance, such as increasing H 2 O 2 concentration in tumor, 148 , 149 and reducing the excessive intracellular antioxidant GSH, 150 can improve efficiency of CDT. 151 In addition, CDT-based combination therapy can be developed, such as CDT-PDT, 152 CDT-PTT, 153 , 154 CDT-chemotherapy, 155 CDT-immunotherapy, 156 CDT-RT, 157 CDT-SDT, 158 CDT-starvation therapy, 159 which can produce significant synergistic effects and reduce the side effects of CDT agents. However, in order to address the current barriers of CDT for clinical applications, we should try to avoid large doses, complex synthesis processes and cumbersome auxiliary devices when designing nanoplatforms.…”
Section: Discussionmentioning
confidence: 99%
“…AFeNPs@CAI CDT MDA-MB-231 [35] FePt@FeOx@TAM-PEG CDT 4T1 [43] UCNP@PVP@MIL88B CDT U87MG [44] H 2 O 2 generation PTCG (EGCG, Pt-OH, PEG-b-PPOH) CDT/Chemotherapy HepG2 [17] Copper hexacyanoferrate CDT 4T1 [40] Den-DOX-Fe 3+ -TA CDT/Chemotherapy U14 [45] PGC-DOX (PEG-GOx, CaCuP, DOX) CDT/Chemotherapy 4T1 [46] ACC@DOX•Fe 2+ -CaSi-PAMAM-FA/mPEG CDT/Chemotherapy A375, 4T1 [47] (MSNs@CaO 2 -ICG)@LA CDT/PDT MCF-7 [48] PZIF67-AT CDT 4T1 [49] Copper peroxide nanodots CDT U87MG [50] GSH depletion FA-Pyrite CDT CT26 [34] MMDM (microphage, MCN, DOX, MnO 2 ) CDT/Chemotherapy 4T1 [51] A@P/uLDHs (artemisinin, PEG, MgFe-LDH) CDT HeLa [52] CCMZ (Cu, CuMoO x , ZP) CDT 4T1 [53] JNP Ve (Au-MnO JNPs, IR1061) CDT/Radiotherapy MCF-7 [54] DMON@Fe 0 /AT CDT 4T1 [55] CMBP (CuO/MnO x @BSA, Pt(IV) prodrug) CDT/Chemotherapy 4T1 [56] Zn x Mn 1−x S/PDA CDT/PTT 4T1 [57] PtCu 3 nanocage CDT/SDT 4T1 [58] External stimuli Light DGU:Fe/Dox CDT/Chemotherapy 4T1 [59] LET-6 (tPy-Cy-Fe, DSPE-PEG) CDT/PTT U87MG [60] GNR@SiO 2 @MnO 2 CDT/PTT U87MG [61] SnFe 2 O 4 nanozyme CDT/PTT/PDT 4T1 [62] MoSe 2 /CoSe 2 @PEG CDT/PTT H-22 [63] HULK (liposome, laccase, MOHQ, FeCe6) CDT 4T1 [64] Cu-OCNP/Lap CDT/PTT HeLa [65] AuPd@Fe x O y CDT/PTT A549 [66] Fe-doped MoO x nanowires CDT/PTT HeLa [67] Hollow magnetite nanoclusters CDT/PTT HeLa [68] ICG@Mn/Cu/Zn-MOF@MnO 2 CDT/PTT/PDT U87 [69] Wesselsite (SrCuSi 4 O 10 ) nanosheets CDT/PTT/Starvation therapy 4T1 [70] MoP 2 nanorods CDT/PTT CAL27 [71] X-ray Cu 2 (OH)PO 4 @PAAS CDT/Radiotherapy HeLa [72] CoFe 2 O 4 nanoparticles CDT/Radiotherapy MCF-7…”
Section: Tme Modulation Ph Modulationmentioning
confidence: 99%
“…Such strategies can be roughly outlined into TME modulation, usage of external stimuli, utilization of chemical and biological stimuli, and design of the nanoplatforms (Table 1). [ 16,17,22,34–36,40,43–105 ]…”
Section: Strategies To Enhance Chemodynamic Therapymentioning
confidence: 99%
“…For example, in our previous research, we found that some nanoparticles, such as superparamagnetic iron oxide nanoparticles (SPIONs), high-Z gold nanoparticles following intratumoral injection can provide a high local concentration of the agent, reduction of the particle clearance (i.e., renal or hepatic clearance) that increases the bioavailability of nanoparticles and has the effect of radiosensitizer in cancer radiotherapy, which can be used for long-term local anti-tumor therapy [ 112 , 113 ]. As an ideal anti-tumor drug candidate, copper-based nanomaterials have the following advantages: (i) compared with other metals, copper is cheap and rich in content [ 114 ], (ii) copper can induce reactive oxygen species (ROS)-mediated oxidative stress and promote tumor cell apoptosis [ 115 , 116 , 117 ], (iii) it has good biocompatibility, biodegradability, antibacterial properties, and selective cytotoxicity to cancer cells [ 118 ], and (iv) copper-based nanomaterials have less toxic effects on normal cells, fewer side effects, and are safer and more reliable [ 119 ]. Thus, copper-based nanomaterials have attracted more and more attention and have become the current research hotspot.…”
Section: Clinical Application Of Copper-based Nanoparticles In Oncologymentioning
confidence: 99%